Genetic Factors Mediate the Impact of Chronic Stress and Subsequent Response to Novel Acute Stress - Terenina, Elena E.; Cavigelli, Sonia; Mormede, Pierre; Zhao, Wenyuan; Parks, Cory; Lu, Lu; Jones, Byron C.; Mulligan, Megan K. (Frontiers in Neuroscience, 2019)
Individual differences in physiological and biobehavioral adaptation to chronic stress are important predictors of health and fitness; genetic differences play an important role in this adaptation. To identify these differences we measured the biometric, neuroendocrine, and transcriptional response to stress among inbred mouse strains with varying degrees of genetic similarity, C57BL/6J (B), C57BL/6NJ (N), and DBA/2J (D). The B and D strains are highly genetically diverse whereas the B and N substrains are highly similar. Strain differences in hypothalamic-pituitary-adrenal (HPA) axis cross-sensitization were determined by plasma corticosterone (CORT) levels and hippocampal gene expression following 7-weeks of chronic mild stress (CMS) or normal housing (NH) and subsequent exposure to novel acute restraint. Fecal CORT metabolites and body and organ weights were also measured. All strains exposed to CMS had reduced heart weights, whereas body weight gain was attenuated only in B and N strains. Acute stress alone produced larger plasma CORT responses in the D and N strains compared to the B strain. CMS paired with acute stress produced cross-sensitization of the CORT response in the N strain. The N strain also had the largest number of hippocampal transcripts with up-regulated expression in response to stress. In contrast, the D strain had the largest number of transcripts with down-regulated expression following CMS and acute stress. In summary, we observed differential responses to CMS at both the physiological and molecular level among genetically diverse strains, indicating that genetic factors drive individual differences in experience-dependent regulation of the stress response.